2010
DOI: 10.1007/s10900-010-9221-1
|View full text |Cite
|
Sign up to set email alerts
|

Exercises in Emergency Preparedness for Health Professionals in Community Clinics

Abstract: Health professionals in community settings are generally unprepared for disasters. From 2006 to 2008 the California Statewide Area Health Education Center (AHEC) program conducted 90 table top exercises in community practice sites in 18 counties. The exercises arranged and facilitated by AHEC trained local coordinators and trainers were designed to assist health professionals in developing and applying their practice site emergency plans using simulated events about pandemic influenza or other emergencies. Of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 3 publications
1
22
0
Order By: Relevance
“…This study [12] though of a larger sample size which share similar areas of concern with regards to MRI safety with the current study clearly demonstrated the lapses on the provision of training on drills necessary to build the capacity of staff working in the MRI suite. Studies have shown that many health professionals are unprepared for a disasters or sometimes even common medical emergencies [13, 14]. The clinical environment is not immune to emergencies as events such as accident, medical event, or trauma; a natural disaster; or an act of violence can occur [15].…”
Section: Discussionmentioning
confidence: 99%
“…This study [12] though of a larger sample size which share similar areas of concern with regards to MRI safety with the current study clearly demonstrated the lapses on the provision of training on drills necessary to build the capacity of staff working in the MRI suite. Studies have shown that many health professionals are unprepared for a disasters or sometimes even common medical emergencies [13, 14]. The clinical environment is not immune to emergencies as events such as accident, medical event, or trauma; a natural disaster; or an act of violence can occur [15].…”
Section: Discussionmentioning
confidence: 99%
“… multi-disciplinary, face-to-face trainings using presentations and case-studies. RR > 6000/9537 (> 62.9) Open ended question; Rating statement Self-assessed knowledge; Self-assessed attitude Fowkes V., 2010, USA, [ 45 ] Health professionals Self-selection & recruitment. Development and application of emergency plans Local health professionals with interest and expertise in emergency preparedness.…”
Section: Methodsmentioning
confidence: 99%
“… - RR > 6000/9537 Satisfaction/methodology: 95% rated modules as good/excellent Self-assessed attitudes: modules reinforced needs for emergency plans; enhanced awareness of possible unusual clinical presentations; enhanced consciousness about infection control. Self-assessed knowledge: modules provided useful approaches to decontamination; - Fowkes V., 2010, [ 45 ] Evaluation forms; assessment of the departments’ emergency plans; AARs completed by the exercise groups; debriefing of coordinators; interviews with trainees; follow-up interviews; quarterly reports by the organizing party RR 1176/1496 System results: 37% of emergency operation plans complete RR 1176/1496 System results: 46% of emergency operation plans complete Satisfaction/methodology: 92–98% rating the training experiences as good to excellent. ; Self-assessed knowledge/skills: 92–98% rates knowledge and skills gained form the exercises as good to excellent.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3] As proxies for actual emergencies, emergency response exercises can improve an organization's employees' fluency with existing plans and can provide opportunities to practice how different organizations and disciplines will work together to respond capably during emergency events. [4][5][6][7] Also, and perhaps most importantly, exercises provide an opportunity to identify specific problems with an organization's emergency planning, training, and/or response that are in need of improvement before an actual disaster event occurs. 1 Unfortunately, the lack of commonly accepted, valid, and reliable measurement processes to use when quantifying the individual elements of performance in an exercise has limited many organizations' ability to feel certain that they have captured and documented the key successes and response challenges from their exercises accurately.…”
Section: Introductionmentioning
confidence: 99%